The multi-kingdom microbiome catalog of the chicken gastrointestinal tract - Yanan Wang; Mengqi Qu; Yuhai Bi; William J. Liu; Sufang Ma; Bo Wan; Yongfei Hu; Baoli Zhu; Gaiping Zhang; George F. Gao (Elsevier, 2024)
Chicken is an important food animal worldwide and plays an important role in human life by providing meat and eggs. Despite recent significant advances in gut microbiome studies, a comprehensive study of chicken gut bacterial, archaeal, and viral genomes remains unavailable. In this study, we constructed a chicken multi-kingdom microbiome catalog (CMKMC), including 18,201 bacterial, 225 archaeal, and 33,411 viral genomes, and annotated over 6,076,006 protein-coding genes by integrating 135 chicken gut metagenomes and publicly available metagenome-assembled genomes (MAGs) from ten countries. We found that 812 and 240 MAGs in our dataset were putative novel species and genera, respectively, far beyond what was previously reported. The newly unclassified MAGs were predominant in Phyla Firmicutes_A (n = 263), followed by Firmicutes (n = 126), Bacteroidota (n = 121), and Proteobacteria (n = 87). Most of the classified species-level viral operational taxonomic units belong to Caudovirales. Approximately, 63.24 % of chicken gut viromes are predicted to infect two or more hosts, including complete circular viruses. Moreover, we found that diverse auxiliary metabolic genes and antibiotic resistance genes were carried by viruses. Together, our CMKMC provides the largest integrated MAGs and viral genomes from the chicken gut to date, functional insights into the chicken gastrointestinal tract microbiota, and paves the way for microbial interventions for better chicken health and productivity.